Efficacy Of Macular Photocoagulation When Given In The Early Or Late Period After Single Intravitreal Bevacizumab Injection In Terms Of Central Foveal Thickness Change And Visual Acuity Gain (Indian Journal of Applied-Basic Medical Sciences, 2021)
AIM: To find out the efficacy of macular photocoagulation when given in the early or late period after  single intravitreal bevacizumab injection in terms of central foveal thickness change and visual acuity  gain. METHODS:40 patient eyes were studied and they were divided into groups based on sex, age, hba1c levels,  severity of disease and treatment received over the period of 6months. RESULT: patients receiving deferred macular photocoagulation after a single intravitreal injection of  bevacizumab had better outcomes regarding reduction of central foveal thickness and improvement in visual  acuity at the end of 6-month observation period compared to those patients receiving prompt macular  photocoagulation.
Keywords: bevacizumab; laser photocoagulation; diabetic retinopathy